Return on assets, return on equity, earnings per share, dividend yield, and book-to-market ratio’s effects on stock return - Annisa Aulia Rahma Atmariani; Dian Agustia (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2024)
This research intends to investigate the ability of Return on assets (ROA), return on equity (ROE), earnings per share (EPS), dividend yield (DY), and book-to-market ratio (BMR) on stock returns. Stock investment is one strategy for investors to channel their finances while boosting wealth due to the high return on equities earned. In this study, company information is represented by financial ratios, which play a significant role in guiding investors in identifying which companies have the potential to give the highest number of returns. With 164 total observations, this research used 56 companies that were part of the LQ45 index on the Indonesian Stock Exchange (IDX) in the 2019–2022 timeframe as a sample study with the aim to examine the effects of ROA, ROE, EPS, dividend yield, and book-to-market ratio on stock return. Using STATA 14.0 software, double linear regression analysis is used in the hypothesis test. The results of this research, as proven by the regression analysis, are as follows: (1) the book-to-market ratio negatively affects stock return; and (2) ROA, ROE, EPS, and dividend yield have no bearing on stock return. This study emphasizes the value of diversifying investment strategies and avoiding a narrow range of financial ratios when choosing which stocks to buy. Investors should evaluate general business conditions and take a wider range of issues into account.